Nagorno Karabakh as an Itegral Part of Soviet Armenia - Hasan-Jalalyan, Stepan R.
The purpose of the article is to show, based on the primary sources and literature related to the issue, whether Azerbaijan ever recognized Artsakh as a part of Armenia, and if so, what significance did it have on the process of settlement of the Azerbaijan-Artsakh conflict? Methods and materials: The article is written through a comparison and comparative study of the original sources related to the issue, as well as an examination analysis of the scientific works related to it. Results: As a result of joint examination of facts and documents related to the issue, as well as historical and political literature, we came to the conclusion that in spite of the decision of the Revolutionary Committee of the Soviet Socialist Republic of Azerbaijan of November 30, 1920, considering Nagorno Karabagh as a part of the Soviet Socialist Republic of Armenia and in spite of the decree of the Council of the People's Commissars of Soviet Armenia adopted on June 12, 1921 that Artsakh was an integral part of Soviet Armenia, the Caucasian Bureau of the Communist Party of Soviet Russia, a political body of a third country, that had no right to resolve territorial issues in this case, without any further discussions or votes, in fact, on 5 July, 1921 illegally adopted a resolution that included Nagorno Karabakh within the borders of Soviet Azerbaijan. На основе первоисточников и литературы по данному вопросу показать признавал ли когда-либо Азербайджан Арцах частью Армении, и если да, то какое значение это имело для процесса урегулирования азербайджано-арцахского конфликта. Методы и материалы: Статья написана путем сопоставления и сравнительного изучения первоисточников, относящихся к проблеме, а также экспертного анализа научных работ, связанных с ней. В результате совместного изучения фактов и документов по данному вопросу, а также историко-политической литературы мы пришли к выводу, что 30 ноября 1920 года решением Революционного Комитета Азербайджанской Советской Социалистической Республики, признанный частью Cоциалистической Республики Советской Армении и согласно декрету, принятому Советом народных комиссаров Советской Армении 12 июня 1921г., Арцах, являющийся неотъемлемой частью Советской Армении, незаконным решением кавказского бюро коммунистической партии Советской России, не обсужденным и не поставленным на голосование партийным органом третьей страны, не имеющей права решать территориальные вопросы, то есть, по сути, не принятым, незаконным решением, был введен в границы Советского Азербайджана.
Keywords: History